The Effect of Infrastructure Development on Economic Growth (Universitas Negeri Semarang, 2022)
The development gap between The Western Indonesia (TWI) and The Eastern Indonesia (TEI) is still quite visible, this gap can be seen from infrastructure development consisting of the Special Allocation Fund (DAK), Long Road Infrastructure (IPJ) and Construction Workforce (TKK). This study aims to determine the effect of infrastructure development on economic growth. The data used is secondary data using panel data regression analysis. This study uses a combination of data between time series data, namely 2015-2019 and cross section data consisting of 34 provinces in Indonesia. The dependent variable used is economic growth, while the independent variables in this study are the Special Allocation Fund (DAK), Long Road Infrastructure (IPJ), Construction Workers (TKK) and the dummy variable, namely the difference between KBI and KTI. The results of the study indicate that DAK has a positive but not significant effect on economic growth. Meanwhile, IPJ and TKK have a positive and significant impact on economic growth. There is also a difference between KBI and KTI that the economic growth is greater in KBI. Kesenjangan pembangunan Kawasan Barat Indonesia (KBI) dan Kawasan Timur Indonesia (KTI) masih cukup terlihat. Kesenjangan tersebut dapat dilihat dari pembangunan infrastruktur yang terdiri dari Dana Alokasi Khusus (DAK), Infrastruktur Panjang Jalan (IPJ) dan Tenaga Kerja Konstruksi (TKK). Data yang digunakan yaitu data sekunder dengan menggunakan analisis regresi data panel. Penelitian ini menggunakan gabungan data antara data time series tahun 2015-2019 dan data cross section dari 34 provinsi di Indonesia. Variabel dependen yang digunakan adalah pertumbuhan ekonomi, sedangkan variabel independen dalam penelitian ini adalah Dana Alokasi Khusus (DAK), Infrastruktur Panjang Jalan (IPJ), Tenaga Kerja Konstruksi (TKK) dan variabel dummy yaitu perbedaan KBI dan KTI. Hasil dari penelitian menunjukkan bahwa DAK memiliki pengaruh positif tetapi tidak signifikan terhadap pertumbuhan ekonomi. Sementara IPJ dan TKK memiliki pengaruh positif dan signifikan terhadap pertumbuhan ekonomi. Terdapat juga perbedaan antara KBI dan KTI lebih besar pertumbuhan ekonominya di KBI.